The impact of patient-held health records on continuity of care among asylum seekers in reception centres: a cluster-randomised stepped wedge trial in Germany - Kayvan Bozorgmehr; Cornelia Straßner; Stefan Noest; Stella Preussler; Rosa Jahn; Sandra Ziegler; Katharina Wahedi (BMJ Global Health)
Introduction The aim of this study was to assess the effectiveness of a patient-held health record (PHR) for asylum seekers on the availability of health-related information.Methods An explorative, cluster-randomised stepped-wedge trial with reception centres as unit of randomisation was conducted. All reception centres (n=6) in two large administrative areas in South Germany with on-site health services were included. All physicians working at these centres were invited to participate in the study. The intervention was the implementation of a PHR. The primary outcome was the prevalence of written health-related information. Secondary outcomes were the physicians’ dissatisfaction with the available written information and the prevalence of missing health-related information. All outcomes were measured at the level of patient–physician contacts by means of a standardised questionnaire, and analysed in logistic multi-level regression models.Results We obtained data on 2308 patient–physician contacts. The presence of the PHR increased the availability of health-related information (adjusted OR (aOR), 20.3, 95% CI: 12.74 to 32.33), and tended to reduce missing essential information (aOR 0.71, 95% CI: 0.39 to 1.26) and physicians’ dissatisfaction with available information (aOR 0.5, 95% CI: 0.24 to 1.04). The availability of health-related information in the post-intervention period was higher (aOR 4.22, 95% CI: 2.64 to 6.73), missing information (aOR 0.89, 95% CI: 0.42 to 1.88) and dissatisfaction (aOR 0.43, 95% CI: 0.16 to 1.14) tended to be lower compared with the pre-intervention period.Conclusions Healthcare planners should consider introducing PHRs in reception centres or comparable facilities. Future research should focus on the impact of PHRs on clinical outcomes and on intersectoral care.Trial registration ISRCTN13212716. Registered 24 November 2016. Retrospectively registered. http://www.isrctn.com/ISRCTN13212716